UNVEILING THE TIKTOK PERSONA: EXPLORING NARCISSISM, SELF-PRESENTATION, AND PERSONALITY TRAITS AMONG USERS - Qudsia Nazir; Aqsa Batool; Gul E Zahra; Dr. Mahrukh Ansar; Gulshan Ali; Nosheen Saba (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The study examined the relationships between narcissism, self-presentation, and personality traits among TikTok users. A cross-sectional study was used by using the Ten Item Personality Inventory (TIPI), the Hypersensitive Narcissism Scale (HSNS), and a Self-Presentation Scale for data collection from a diverse sample of TikTok participants. Correlation analyses revealed significant relationships, with self-presentation negatively correlated with hypersensitive narcissism and personality traits, while a positive correlation existed between narcissism and personality traits. Independent t-tests indicated that users under 30 exhibited higher self-presentation levels and lower narcissism scores compared to those over 30. Furthermore, users with more than 1,000 followers demonstrated higher self-presentation and personality traits than those with fewer followers. Linear regression analyses confirmed that personality traits positively predicted self-presentation and negatively predicted narcissism. These findings suggest that individuals with stronger personality traits engage in more effective self-presentation while displaying lower narcissistic tendencies. The results contributed to understanding TikTok personas, emphasizing the dynamic interplay of personality and self-presentation in social media contexts. Future research should further explore the implications of these relationships on mental health and social dynamics among diverse age groups.